Research on negative pressure jet dust-removal water curtain technology for coal mine cleaner production. (15th February 2022) - Peng, Huitian; Nie, Wen; Zhang, Shaobo; Cheng, Weimin; Liu, Qiang; Guo, Cheng; Ma, Qingxin; Zhou, Zhongliang; Xu, Changwei; Hua, Yun; Zhang, Hao
Graphical abstract: Highlights: The negative pressure jet dust-removal water curtain was developed. We optimized the nozzles and verified through a spray experiment–CFD simulation. We obtained distribution law of spraying field and best parameters by CFD. The water curtain can effectively settle the respirable dust in air return roadways. Abstract: There are serious pollution problems in the underground working environment of coal mines. To address this problem, a type of negative pressure jet dust-removal water curtain, based on the negative pressure jet dust-removal principle, was developed. Spray experiments were performed to obtain the macro- spray parameters of each nozzle, which were then used as parameters for CFD (computational fluid dynamics) modeling to numerically simulate the spray field. The influence of spray pressure Pw, nozzle type Tn, and the distance between the nozzle opening and the air suction port Ls, on the suction and purification effect and the spray field distribution law were studied. These studies determined that the air suction volume and spray field coverage effect were optimal when the parameter settings were Pw  = 6 MPa, Tn :III, and Ls  = 6 cm. Under such circumstances, the air suction volume of the dust hood was as high as 13.74 m 3 /min, and the proportion of the spray field with a cross-section concentration at the water curtain of more than 10 4 mg/m 3 accounted for 92.4%. This dust reduction effect was physically measured in the air return roadway of the 117 fully mechanized mining face of Jinjitan Coal Mine. Using the optimal parameters obtained through numerical simulation, the concentration of respirable dust at measuring point C # was measured to be 0.179 mg/m 3, equal to a dust reduction rate of 90.4%. This indicates that the application of a negative pressure jet dust-removal water curtain in large cross-section roadways can significantly reduce dust pollution levels.